Barrierless single-electron-induced cis-trans isomerization - Klaiman, Shachar; Cederbaum, Lorenz S. (Angewandte Chemie. International edition, 2015)
Lowering the activation energy of a chemical reaction is an essential part in controlling chemical reactions. By attaching a single electron, a barrierless path for the cis-trans isomerization of maleonitrile on the anionic surface is formed. The anionic activation can be applied in both reaction directions, yielding the desired isomer. We identify the microscopic mechanism that leads to the formation of the barrierless route for the electron-induced isomerization. The generalization to other chemical reactions is discussed.
Gesehen am 07.07.2020